Charter schools and accountability in public education - Hill, Paul T. (Paul Thomas), 1943- (Brookings Institution Press, 2002)
"Charter schools are not fundamentally different from public magnet and specialty schools, yet their systems of accountability are unique - and controversial. Unlike public schools, charter schools enter into performance agreements with local school boards or other state agencies. If their students do not learn, the schools can be denied further public funds. In return for entering these performance agreements, charter schools are exempt from some regulations that apply to conventional public schools." "This book examines charter school accountability in theory and in fact. It represents an early effort to understand how new forms of accountability for public education actually work, in the process drawing lessons that are especially relevant to the standards-based reform movement." "The authors examined 150 schools and 60 authorizing agencies in six states: Arizona, California, Colorado, Georgia, Massachusetts, and Michigan. They conducted extensive case studies of internal accountability relationships in 17 of the 150 schools, interviewing school principals, teachers, staff members, parents, governing board members, and authorizing agency officials. They supplemented the results of state and school case studies with data from a nationally representative survey of charter schools."--Jacket